Ozone influences migration and proliferation of neural stem cells in vitro. (20th November 2020) - Tricarico, Gerardo; Isakovic, Jasmina; Song, Min Suk; Rustichelli, Franco; Travagli, Valter; Mitrecic, Dinko
Highlights: Ozone increases neural stem cell migration and cytokine release. To a smaller extent, ozone also increases neural stem cell proliferation. Due to its electrical properties, ozone has a potential use in neurorestoration. Abstract: Ozone (O3 ) is a short-lived molecule which can be produced in a controlled reaction when oxygen is exposed to electric discharge. In the last few decades, many publications dealing both with animals and humans reported beneficial effects of ozone administration linked to its immunomodulatory and protective role against cellular damage. This is the first work which brings insight into how ozone influences cells of neural lineage in vitro and hypothesizes the potential molecular and novel electromagnetic mechanisms behind its action. By using neural stem cells, we show that ozone, especially in concentrations of around 11 μg/mL, significantly increases the speed of neural cell migration. With much lower effects, it also increases cell proliferation and cytokine production. Results of this study, at least partly, explain the observed beneficial effects of ozone in diseases of the nervous system tested on animal models and in human clinical trials. Therefore, here described effects of ozone on cellular level represent a firm basis for further investigation of possible applications of ozone in regeneration of the nervous system.